2021
DOI: 10.1021/acssynbio.1c00204
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of DNA Target Formulations by CRISPR-Cas12a Using a dsDNA Reporter

Abstract: CRISPR-Cas12a is a powerful platform for DNA-based diagnostics. The detection scheme relies on unselective shredding of a fluorescent ssDNA reporter upon target DNA recognition. To extend the reporter library beyond ssDNAs, we discovered a fluorescent reporter type using a dsDNA template. In this design, the fluorescence of the dsDNA reporter is quenched via contact-quenching mechanism. Upon detection, the quenched fluorescence recovers with the activation Cas12a complex. Here, we compared the probing performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 41 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…[10b, 22] The collateral activity against short dsDNA substrate is mainly attributed to the instability of the dsDNA reporter. [22] However, our results showed that long and stable ds λ DNA could also be significantly trans-degraded by Cas12a.…”
Section: Resultsmentioning
confidence: 64%
“…[10b, 22] The collateral activity against short dsDNA substrate is mainly attributed to the instability of the dsDNA reporter. [22] However, our results showed that long and stable ds λ DNA could also be significantly trans-degraded by Cas12a.…”
Section: Resultsmentioning
confidence: 64%
“…This is an improvement to typical CRISPR-alone methods where detection limit is about 10 pM. [26][27][28] To demonstrate the amplification validity of HCR, we re-run the study with traditional F and Q-labeled ssDNA probe (5′ FAM-TTATT-3′ Iowa BlackFQ, i.e. 'ssprobe') instead of fHCR, where we were only able to detect 50 pM of dsDNA HBV , a 100-fold depreciation than CRISPR-fHCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9,[29][30][31][32][33] Additionally, the FQ-reporter has certain defects, including photobleaching, high background signals, and low stability. 34,35 Based on this status quo, the reporter innovation has sprung up, which provided few alternative reporter forms, such as nanomaterial-medicated reporters, 36,37 double-stranded reporters, 38 and G-quadruplex reporters. 39,40 For example, gold nanoparticle-functionalized reporters have been developed; however, costly labels and harsh synthetic conditions have limited their applications.…”
Section: Introductionmentioning
confidence: 99%